Cash Waqf Literacy in Islamic Higher Education: An Epistemic Perspective from Indonesia and Malaysia - Mutho'am; Akmal Bashori; Herman Sujarwo; Nor Adila binti Mohd Noor; Nor Faezah Ghazi Ahmad (Al-Muamalat, 2026)
Cash waqf is an important instrument for Islamic social finance, but the optimal realization in higher education is affected by fragmented student literacy. A persistent gap remains in bridging traditional Islamic jurisprudence with modern digital frameworks. Therefore, this study aimed to analyze and compare the levels and drivers of cash waqf literacy in Islamic higher education institutions in Indonesia and Malaysia. Data from students at Universitas Sains Al-Qur’an (UNSIQ), Indonesia, and Universiti Teknologi MARA Terengganu Branch (UiTMCT), Malaysia, were evaluated using PLS-SEM and Multi-Group Analysis, complemented by qualitative insights through the adoption of a sequential explanatory design. The results showed that UNSIQ students reported strong conceptual mastery grounded in fiqh turāṡ but lacked understanding of modern technical innovations. Conversely, UiTMCT students exhibited functional literacy driven by institutional authority and digital technology, with limited reflection on classical normative foundations. The results suggested a failure of epistemic integration between Islam’s normative spiritual values and modern instrumental rationality. This study proposed an “integrative cash waqf literacy” framework synergizing fiqh turāṡ, institutional governance, and digital innovation to strengthen students' roles in Islamic philanthropy. Future studies should expand samples across broader institutions and use longitudinal designs to explore digital interventions in improving sustainable cash waqf literacy.